2017
DOI: 10.3332/ecancer.2017.774
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section evaluation of sentinel lymph nodes in breast carcinoma: a retrospective analysis

Abstract: ObjectiveTo determine the false-negative rate, sensitivity, and diagnostic accuracy of the frozen section analysis of the sentinel lymph node (SLN) biopsy in early-stage breast cancer compared to the definitive section and to identify the factors that could be associated with the appearance of false-negative cases. Secondarily, to evaluate the pathological results of cases submitted to completion axillary lymph node dissection (ALND) for positive SLN.MethodsWe performed a five-year review of cases (2011–2015),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…They showed that TIC had lower sensitivity but much greater specificity, which is not in agreement with our findings 22 . Russo et al demonstrated that FSA had an acceptable false‐negative rate during SLN biopsy 23 . Regardless of the diagnostic value of each technique, the cost of each technique is also critical for both healthcare providers and patients.…”
Section: Discussioncontrasting
confidence: 57%
“…They showed that TIC had lower sensitivity but much greater specificity, which is not in agreement with our findings 22 . Russo et al demonstrated that FSA had an acceptable false‐negative rate during SLN biopsy 23 . Regardless of the diagnostic value of each technique, the cost of each technique is also critical for both healthcare providers and patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, one of the most consistent features associated with SLN FS FN in the literature is small ( 2 mm) micrometastasis. [24][25][26][27] In this study, SLN FS FN was seen in 21 patients, comprising 4.8% of all cases and 22.5% of all cases with final positive SLN status. However, most (14 of 21; 66.7%) were micrometastases, and 4 patients with macrometastases had other intraoperatively identified positive SLNs, 3 of whom underwent ALND during the same procedure and 1 of whom had her intraoperative course dictated by trial protocol.…”
Section: Discussionmentioning
confidence: 52%
“…False negative patients that are more likely to detect metastasis like micro metastasis or isolated tumor cell or have less 2 lymph nodes involvement, however, re-surgical procedures can be discarded. In fact, the use of new protocols to deal with different situations of lymph node involvement can prevent the complications of axillary dissection and reduce the stress of patients due to the need for re-surgery, and therefore the use of frozen section is not necessary and in this study, has not reduced the risk of re-surgery (Russo et al, 2017;van der Noordaa et al, 2017). One of the shortcomings of this study was the low number of patients.…”
Section: Discussionmentioning
confidence: 84%